2002
DOI: 10.1177/1359104502007004006
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Related to Child and Parental Psychopathology: A Descriptive Review of the Literature

Abstract: Two areas of recent research on parenting are examined: (i) Parenting problems in families with parental psychopathology, and (ii) parenting problems when children have psychiatric disorders. Review of literature showed that parental, as well as child, psychopathology represents major stressors for a family and substantially impacts parenting abilities. Two main dimensions of dysfunctional parenting occur in families with child or parental psychopathology: (i) Parental negativity, and (ii) various forms of ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
183
3
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(205 citation statements)
references
References 151 publications
9
183
3
10
Order By: Relevance
“…14 There is some evidence that maternal depression may be more closely associated with disrupted parenting quality than paternal depression. 15 Mothers with depression may show decreased sensitivity to their children's needs, 16 and changes in maternal behavior have been found to mediate the association between maternal depression and toddlers' behavioral problems. 17 Couple conflict is another potential mechanism of risk transmission.…”
Section: What This Study Addsmentioning
confidence: 99%
“…14 There is some evidence that maternal depression may be more closely associated with disrupted parenting quality than paternal depression. 15 Mothers with depression may show decreased sensitivity to their children's needs, 16 and changes in maternal behavior have been found to mediate the association between maternal depression and toddlers' behavioral problems. 17 Couple conflict is another potential mechanism of risk transmission.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Several studies (e.g., Barber et al, 2005;Berg-Nielsen, Vikan, & Dahl, 2002) have shown that high parental support and low parental control are associated with higher levels of adaptive psychosocial functioning (e.g., competence, self-regulation, and academic achievement) and lower levels of internalizing and externalizing problem behaviors. In relation to NSSI behaviors, Bureau et al (2010) found a positive association between NSSI and perceived parental control, and a negative association between NSSI and perceived support.…”
Section: Interpersonal Correlates Of Nssimentioning
confidence: 99%
“…Growing up with parents who suffer from various kinds of psychopathology is a known risk factor; parental psychopathology has been linked with negative child outcomes such as psychopathology in children and lower scores on various measures of adjustment (Berg-Nielsen, Vikan, & Dahl, 2002;Luthar, Cicchetti, & Becker, 2000). Furthermore a link between major depression in parents and attachment classification in children has been established (Seifer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%